2013
DOI: 10.1007/s10620-013-2969-2
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of KIF3B Expression Inhibits Human Hepatocellular Carcinoma Proliferation

Abstract: Background Human hepatocellular carcinoma (HCC) is one of the most common fatal cancers and an important health problem worldwide, but its mechanism is still unclear. Microtubule (MT) kinesin motor proteins orchestrate a variety of cellular processes (e.g. mitosis, motility and organelle transportation) and have been involved in human carcinogenesis. KIF3B, the kinesin superfamily of proteins (KIFs), plays an important role in the regulation of mitotic progression. Aim The expression of KIF3B and its involveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…After 48 hours, cells were harvested with trypsin and washed 2 times in ice-cold PBS, resuspended in 100 μl of binding buffer and incubated with Annexin V-FITC (4 A Biotech, China) for 5 min at 4 °C in the dark. After staining, the cells were incubated with propidium iodide for 5 min at 4 °C in the dark and then assayed with a flow cytometer (Beckman Coulter, Germany) 42 cell cycle. Cell cycle analysis was performed with a cell cycle kit (Shanghai BestBio, China) according to the manufacture's instructions 43 .…”
Section: Methodsmentioning
confidence: 99%
“…After 48 hours, cells were harvested with trypsin and washed 2 times in ice-cold PBS, resuspended in 100 μl of binding buffer and incubated with Annexin V-FITC (4 A Biotech, China) for 5 min at 4 °C in the dark. After staining, the cells were incubated with propidium iodide for 5 min at 4 °C in the dark and then assayed with a flow cytometer (Beckman Coulter, Germany) 42 cell cycle. Cell cycle analysis was performed with a cell cycle kit (Shanghai BestBio, China) according to the manufacture's instructions 43 .…”
Section: Methodsmentioning
confidence: 99%
“…In addition to KIF15 of this study, a variety of KIFs are reported to be involved in tumor progression. In previous studies, KIF1B, KIF3B, and KIF14 promoted growth of hepatocellular carcinoma and was correlated with the prognosis of hepatocellular carcinoma patients [24][25][26]. KIF3B was involved in the migration of seminoma cancer cells [27].…”
Section: Discussionmentioning
confidence: 81%
“…All of the stained sections were evaluated in a blinded manner by two independent senior pathologists without any clinicopathological variables of the patients (17). Five high-power fields (Leica microscope Germany) were selected randomly and >300 cells in each field were counted to determine the labeling index (LI), which means the percentage of immunostained cells relative to the total number of cells (18). Intensity was evaluated in comparison with the control and scored as follows: 0, negative staining; 1, weak staining; 2, moderate staining; 3, strong staining.…”
Section: Methodsmentioning
confidence: 99%